On Geodesic Equation and Main Scalar in Two Dimensional Finsler Space with Matsumoto Metrics (Journal of Informatics and Mathematical Sciences, 2018)
In this paper, we consider the two dimensional Finsler space with generalized Matsumoto metric and derived the geodesics equation in the Weierstrass form of differential equation. Then we find the main scalar for generalized Matsumoto metric in the two dimensional Finsler space.
Keywords: \((α; β)\)-metrics; Geodesics; Two-dimensional Finsler space; Main scalar; Matsumoto metric